ANALISIS SEKTOR UNGGULAN PERTANIAN PADA PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN SINTANG TAHUN 2006-2010 - B01106108, RYAN HIDAYAT (Jurnal Pembangunan dan Pemerataan, 2013)
Problems of this study is "How can the Agricultural Sector Development in Sub Sintang of the year 2006-2010". The purpose of this study was to determine and analyze the sub-sectors be seen from the growth and contribution during 2006-2010 in Sintang, knowing the projected contribution of agriculture sector sub period of 10 (ten) years in Sintang and map the agricultural sub-sectors based on growth Sintang and its contribution. In this study the authors used descriptive and qualitative methods in which the data used are secondary data obtained from the Central Bureau of Statistics of West Kalimantan Province. In connection with this skripisi discussion, the authors use the LQ analysis, Shift Share, Projection, and the typology of the problems Klassen answer for this thesis. From these results we got the result that the agricultural sector has a major contribution from other sectors, while high growth sub-sector and sub ??sector contribution is plantation. Therefore, these two sectors and sub ??sectors are leading or are in Sintang basis and potential for development as the economy pengerak Sintang district, so as to compete with other districts and is expected to also be able to export out of the other provinces. With appropriate government policies and taking advantage sectors and sub ??sectors expected to memdorong owned economic growth so as to achieve a better Sintang district and advanced.